2012
DOI: 10.4315/0362-028x.jfp-11-367
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chlorine, Blanching, Freezing, and Microwave Heating on Cryptosporidium parvum Viability Inoculated on Green Peppers

Abstract: Cryptosporidium parvum oocysts have been found on the surface of vegetables in both developed and developing countries. C. parvum can contaminate vegetables via various routes, including irrigation water. This study investigated the effect of individual treatments of chlorine, blanching, blast freezing, and microwave heating, as well as combined treatments of chlorine and freezing, and chlorine and microwave heating on the viability of C. parvum oocysts inoculated on green peppers. The viability of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 29 publications
1
13
0
1
Order By: Relevance
“…Protozoan parasites, such as Cryptosporidium parvum and Cyclospora cayetanensis, have also been associated with outbreaks related to fresh produce consumption, and countries in Latin America have recognized them as pathogens of concern (4,67,70,71). If produce wash water should be kept free of these pathogens, a chlorination system would fail due to the high level of resistance to chlorine (72,73), or alternatively, excessively Van Haute et al high free chlorine concentrations would be required. Ozone (74), UV (75), and, especially for avoiding cross-contamination in washing processes, the more stable chlorine dioxide (6,32,76,77) are better alternatives to chlorine for inactivation of protozoan parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Protozoan parasites, such as Cryptosporidium parvum and Cyclospora cayetanensis, have also been associated with outbreaks related to fresh produce consumption, and countries in Latin America have recognized them as pathogens of concern (4,67,70,71). If produce wash water should be kept free of these pathogens, a chlorination system would fail due to the high level of resistance to chlorine (72,73), or alternatively, excessively Van Haute et al high free chlorine concentrations would be required. Ozone (74), UV (75), and, especially for avoiding cross-contamination in washing processes, the more stable chlorine dioxide (6,32,76,77) are better alternatives to chlorine for inactivation of protozoan parasites.…”
Section: Discussionmentioning
confidence: 99%
“…An investigation of the efficacy of different treatments used in food processing (i.e. chlorine, blanching, blast freezing and microwave heating) on the viability of C. parvum has showed that oocysts can be destroyed by heat and, to some extent, by freezing, but not by safe concentrations of chlorine (Duhain et al, 2012). Usually, Giardia cysts are more susceptible to chlorine disinfection than Cryptosporidium oocysts (Sterling, 1990).…”
Section: Transmissionmentioning
confidence: 99%
“…When microwaves are applied at certain frequencies, with high energy and for a sufficiently long period of time, their thermal effect is most likely dominant and kills bacterial cells or yeasts. Numerous experiments with microwave irradiation of various cultures of bacteria and yeasts in a wet environment such as a water suspension did not show additional killing of the microbes by microwaves compared to that caused by conventional heating to the same temperature [8,9,10]. However, in a dry environment, the killing effect of microwave radiation was significantly decreased and happened only after a prolonged period of irradiation, most likely due to a lower transformation of microwave energy to heat.…”
Section: Overall Effects On Growthmentioning
confidence: 99%